Bibliometric Analysis: Development of Scientific Publications on "Islamic Education" Based on Titles in the Scopus Database 1980-2023 - Amin, Khoirul; Ni'mah, Zulfatun; Susanto, Ari (Maharot : Journal of Islamic Education, 2023)
This research aims to be used in the preparation of writing advanced scientific articles about Islamic education based on the title by knowing the main information about the article, 1) most information, most citation, most relevant author, 2) reviewing the development of publications from 1980-2023, 3) fade most relevant affiliates, 4) co-occurrence network by title, source title, theme development, trending topics by title, and 5) wordcloud by title, thematic maps or future research theme opportunities. The tool used to analyze the data in this study was part of rR-studio, namely the bibliometric r-package software. The data analyzed were obtained from the Scopus database with the type of article title document obtained from CSV which was then analyzed using the Biblio Shiny Web Interface. The results of a bibliometric analysis on Islamic education based on titles from 1980-2023, provide an illustration that scientific articles on Islamic education have developed quite rapidly from year to year and are quite popular in the world of global academics on the Asian continent where the majority of the population is Muslim. The affiliates that are most active in publishing scientific studies on Islamic education are still dominated by universities on the Asian Continent, such as the National University of Malaya, the University of Malaya and the Indonesian University of Education. The discussion of scientific research on Islamic education raises many themes related to the social field in general, such as education and students.